TRPV1 Antagonist Prevents Neonatal Sevoflurane-Induced Synaptic Abnormality and Cognitive Impairment in Mice Through Regulating the Src/Cofilin Signaling Pathway - Liu, Yuqiang; Yang, Han; Fu, Yifei; Pan, Zhenglong; Qiu, Fang; Xu, Yanwen; Yang, Xinping; Chen, Qian; Ma, Daqing; Liu, Zhiheng (Frontiers in Cell and Developmental Biology, 2021)
Long-term neurodevelopmental disorders following neonatal anaesthesia have been reported both in young animals and in children. The activation of transient receptor potential vanilloid 1 (TRPV1) channels in hippocampus adversely affects neurodevelopment. The current study explored the underlying mechanism of TRPV1 channels on long-lasting cognitive dysfunction induced by anaesthetic exposure to the developing brain. we demonstrated that TRPV1 expression was increased after sevoflurane exposure both in vitro and in vivo. Sevoflurane exposure to hippocampal neurons decreased the synaptic density and the surface GluA1 expression, as well as increased co-localisation of internalized AMPAR in early and recycling endosomes. Sevoflurane exposure to newborn mice impaired learning and memory in adulthood, and reduced AMPAR subunit GluA1, 2 and 3 expressions in the crude synaptosomal fractions from mouse hippocampus. The inhibition of TRPV1 reversed the phenotypic changes induced by sevoflurane. Moreover, sevoflurane exposure increased Src phosphorylation at tyrosine 416 site thereby reducing cofilin phosphorylation. TRPV1 blockade reversed these suppressive effects of sevoflurane. Our data suggested that TRPV1 antagonist may protect against synaptic damage and cognitive dysfunction induced by sevoflurane exposure during the brain developing stage.